2013
DOI: 10.1074/jbc.m112.436741
|View full text |Cite
|
Sign up to set email alerts
|

70-kDa Heat Shock Cognate Protein hsc70 Mediates Calmodulin-dependent Nuclear Import of the Sex-determining Factor SRY

Abstract: Background: Sex determining factor SRY possesses dual nuclear import mechanisms, with its CaM-dependent mechanism being poorly understood. Results: hsc70 enhances CaM-dependent nuclear accumulation of SRY through its ability to bind the SRY⅐CaM complex, dependent on Ca 2ϩ . Conclusion: hsc70 is a key mediator of the CaM-dependent nuclear transport mechanism of SRY. Significance: hsc70 may mediate nuclear transport of other developmentally important transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Finally, we evaluated the intranuclear mobility of GFP‐STAT3α and ‐STAT3β under both basal and cytokine‐stimulated conditions using FRAP. In contrast to the above analysis where bleaching of a large region of the nucleus essentially eliminates the potential complication of an effect of intranuclear mobility, here we bleached a small region within the nucleus, and the recovery of fluorescence in this bleached intranuclear area ( F in ) followed for 100 seconds (Figure ), to enable intranuclear dynamics to be assessed directly . Both proteins showed fluorescence ( F in ) recovery under both basal and cytokine‐stimulated conditions, as evident from the representative images and quantitative analysis (Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, we evaluated the intranuclear mobility of GFP‐STAT3α and ‐STAT3β under both basal and cytokine‐stimulated conditions using FRAP. In contrast to the above analysis where bleaching of a large region of the nucleus essentially eliminates the potential complication of an effect of intranuclear mobility, here we bleached a small region within the nucleus, and the recovery of fluorescence in this bleached intranuclear area ( F in ) followed for 100 seconds (Figure ), to enable intranuclear dynamics to be assessed directly . Both proteins showed fluorescence ( F in ) recovery under both basal and cytokine‐stimulated conditions, as evident from the representative images and quantitative analysis (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…FRAP and intranuclear dynamics analyses were carried out, as mentioned previously , using identical parameters to those above, but with a smaller bleached area (∼10%) and images collected every 5 seconds for a period of 100 seconds. The fluorescence in the bleached small nuclear region ( F in ) was determined by image analysis as above, and FRAP results were presented in terms of fractional recovery of F in (values at each time interval divided by average pre‐bleach value) and data were fitted exponentially according to the formula y = a (1 − e − bx ) to determine the maximal recovery (corrected for the loss of total cellular fluorescence due to the bleach process) and half‐time ( t 1/2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hsp70 is a molecular chaperone essential to protein transport during cellular stress, including inflammation and autoimmune conditions (Jolesch et al, 2012). Hsp70 has been implicated in the nuclear import of multiple proteins, including NF-B (Fujihara and Nadler, 1999), the temperature sensitive p53 mutant (Akakura et al, 2001), p38 MAPK (Gong et al, 2012), Simian virus 40 large tumor antigen (Yang and DeFranco, 1994), nucleoplasmin (Imamoto et al, 1992) and the sex-determining factor SRY (Kaur et al, 2013). Hsp70 also facilitates the nuclear export of importins (Kose et al, 2005;Miyamoto et al, 2004), which have been shown to mediate the nucleocytoplasmic transport of the intracellular domain of Notch1 (Huenniger et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dr. Murakami has demonstrated the critical regulation of SRY for Sgf29 gene expression in rodent HCC [2]. Additionally, evidence has indicated the heat shock protein can promote the nucleic translocation of SRY [7]. Therefore, the upstream and downstream of SRY regulation are potentially complex in HCC.…”
Section: Replymentioning
confidence: 95%